Mechanisms underlying superior memory of skilled climbers in indoor bouldering - Medernach, J. P.; Henz, J.; Memmert, D. (Journal of Sports Sciences, 2023)
Introduction Bouldering is an Olympic climbing discipline that encompasses short climbing sequences, referred to as boulders, set up on low-height bouldering walls. Memory plays a critical role in bouldering, as it allows climbers to develop climbing strategies, to mentally rehearse climbing movements, and to recall climbing holds of boulders. This study extends previous research on memory in climbing and bouldering with the purpose to elucidate potential mechanisms underlying superior memory abilities of skilled climbers.